1995
DOI: 10.1063/1.469394
|View full text |Cite
|
Sign up to set email alerts
|

A guided-ion beam study of the hydrogen atom transfer reaction of state-selected N+2 with H2 at collision energies ranging from subthermal to 2 eV (c.m.)

Abstract: This article presents detailed internal and kinetic energy dependent cross sections and reaction rates for the hydrogen atom transfer processes N+2(X 2Σ+g, v+=0–4, J+=2)+H2→N2H++H, which were obtained under single-collision conditions in a guided-ion beam/scattering gas experiment. Preparation of ions in specific states relied on single-color excitation within a resonantly enhanced (2+1) multiphoton ionization scheme. The translational energy of the ions, Elab, was varied from 0.1 eV to approximately 30 eV. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…At 150 K, it is about 1.3 × 10 −9 cm 3 s −1 , which is our recommended value for Titan's ionosphere. Knott et al (1995) measured the cross section as a function of collision energy and found two regimes: it follows an E −0.5 CM law for E CM = 8-90 meV and an E −0.33 CM law for E CM = 90 meV to 2 eV. These authors did not observe a variation of the rate constant with the vibrational level of N + 2 .…”
Section: (±25%)mentioning
confidence: 83%
See 2 more Smart Citations
“…At 150 K, it is about 1.3 × 10 −9 cm 3 s −1 , which is our recommended value for Titan's ionosphere. Knott et al (1995) measured the cross section as a function of collision energy and found two regimes: it follows an E −0.5 CM law for E CM = 8-90 meV and an E −0.33 CM law for E CM = 90 meV to 2 eV. These authors did not observe a variation of the rate constant with the vibrational level of N + 2 .…”
Section: (±25%)mentioning
confidence: 83%
“…For ground-state reactants, the reaction proceeds at thermal energies with the rate predicted by the Langevin classical ion-molecule capture theory (1.56 × 10 −9 cm 3 s −1 ). Vibrational excitation of the N + 2 appears to have only minor effects on the reaction rates (de Gouw et al 1995;Knott et al 1995). As far as the electronic excitation is concerned, the reaction rate for N + 2 in the first electronically excited A 2 Π u state is 50% lower with respect to the X state (Uiterwaal et al 1995).…”
Section: (±25%)mentioning
confidence: 90%
See 1 more Smart Citation
“…11 This diagram shows the high density of exiting channels, which may complicate the studies for this system. Experimentally, the following channels have been investigated: 6,10,[12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…6,10,15,16,29 Absolute cross sections are available for processes ͑1͒-͑3͒ from thermal to high collision energies. The final products may carry some internal energy or not corresponding to their electronic and/or vibrational and/or rotational excitation during these reactions.…”
mentioning
confidence: 99%